Accelerate Clinical Trials in Charcot-Marie-Tooth Disease (ACT-CMT): A Protocol to Address Clinical Trial Readiness in CMT1A - Eichinger, Katy; Sowden, Janet E.; Burns, Joshua; McDermott, Michael P.; Krischer, Jeffrey; Thornton, John; Pareyson, Davide; Scherer, Steven S.; Shy, Michael E.; Reilly, Mary M.; Herrmann, David N. (Frontiers in Neurology, 2022)
Background With therapeutic trials on the horizon for Charcot-Marie-Tooth type 1A (CMT1A), reliable, valid, and responsive clinical outcome assessments and biomarkers are essential. Accelerate Clinical Trials in CMT (ACT-CMT) is an international study designed to address important gaps in CMT1A clinical trial readiness including the lack of a validated, responsive functional outcome measure for adults, and a lack of validated biomarkers for multicenter application in clinical trials in CMT1A. The primary aims of ACT-CMT include validation of the Charcot-Marie-Tooth Functional Outcome Measure, magnetic resonance imaging of intramuscular fat accumulation as a lower limb motor biomarker, and in-vivo reflectance confocal microscopy of Meissner corpuscle sensory receptor density, a sensory biomarker. Initial studies have indicated that these measures are feasible, reliable and valid. A large prospective, multi-site study is necessary to fully validate and examine the responsiveness of these outcome measures in relation to existing outcomes for use in future clinical trials involving individuals with CMT1A. Two hundred fifteen adults with CMT1A are being recruited to participate in this prospective, international, multi-center study. Serial assessments, up to 3 years, are performed and include the CMT-FOM, CMT Exam Score-Rasch, Overall Neuropathy Limitations Scale, CMT-Health Index, as well as nerve conduction studies, and magnetic resonance imaging and Meissner corpuscle biomarkers. Correlations using baseline data will be examined for validity. Longitudinal analyses will document the changes in function, intramuscular fat accumulation, Meissner corpuscle sensory receptor density. Lastly, we will use anchor-based and other statistical methods to determine the minimally clinically important change for these clinical outcome assessments and biomarkers in CMT1A. Reliable, and responsive clinical outcome assessments of function and disease progression biomarkers are urgently needed for application in early and late phase clinical trials in CMT1A. The ACT-CMT study protocol will address this need through the prospective, longitudinal, multicenter examination in unprecedented detail of novel and existing clinical outcome assessments and motor and sensory biomarkers, and enhance international clinical trial infrastructure, training and preparedness for future therapeutic trials in CMT and related neuropathies